Postural alteration in sedestation and its association to lumbar pain in the administrative staff of hospital III Daniel Alcides Carrión - Essalud Tacna 2017 - Quispe Parra, Maribel (2019)
A study carried out to measure whether the postural alteration is associated with low back pain in the administrative staff of Hospital III Daniel Alcides Carrión Essalud Calana - Tacna 2017. Observational, analytical, prospective and cross-sectional research at the relational level. We worked with the total of the administrative staff of Hospital III Daniel Alcides Carrión Essalud Calana - Tacna 2017, who met the inclusion and exclusion criteria of those who collected the data of the postural tab for sitting, duly validated and filled out by the participants. It was found that in the first 10 hours of the morning, the intermediate and anterior positions predominate in the increase of pain and in the following hours it is the anterior position that exacerbates the pain followed by the intermediate one. There is no significant difference with the variable nutritional status of workers and linkage with low back pain. There is a directly proportional relationship between pain intensity and working hours (p: 0.03). A significant difference is observed in the evolution of pain at 12:30 pm. According to sex, the pain is greater in the female staff, time of service (p: 0.002) and early work days especially in the staff with service time of 21 years to more.